2012
DOI: 10.1016/j.envsoft.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of eight metamodeling techniques for the simulation of N2O fluxes and N leaching from corn crops

Abstract: The environmental costs of intensive farming activities are often underestimated or not traded by the market, even though they play an important role in addressing future society's needs. The estimation of nitrogen (N) dynamics is thus an important issue which demands detailed simulation based methods and their integrated use to correctly represent complex and nonlinear interactions into cropping systems. To calculate the N 2 O flux and N leaching from European arable lands, a modeling framework has been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 72 publications
(84 reference statements)
0
55
0
3
Order By: Relevance
“…Various emulators based on statistical learning have already been developed in the climate and environmental modeling community for the last few years (e.g., [22,35,36,[39][40][41][42][43]). These emulators have in common that they were developed from adaptive, flexible nonparametric regression algorithms, typically within the family of machine learning regression algorithms (MLRAs) [44].…”
Section: Emulator Theorymentioning
confidence: 99%
“…Various emulators based on statistical learning have already been developed in the climate and environmental modeling community for the last few years (e.g., [22,35,36,[39][40][41][42][43]). These emulators have in common that they were developed from adaptive, flexible nonparametric regression algorithms, typically within the family of machine learning regression algorithms (MLRAs) [44].…”
Section: Emulator Theorymentioning
confidence: 99%
“…Studies have shown mixed model performance in simulating N 2 O emissions under different climate and management conditions (Frolking et al, 1998;Li et al, 2005;Villa-Vialaneix et al, 2012;Vogeler et al, 2013). Comparisons of the different N 2 O emission algorithms can improve our understanding of N 2 O emissions.…”
Section: Introductionmentioning
confidence: 97%
“…Among meta-modelling approaches [30,31], two were investigated: a multiple polynomial linear metamodel (PLMM, Faivre, unpublished) and a generalized additive model (GAM; Woods, 2006). The first meta-model, PLMM, aims at modelling the simulated STAR variable as a linear combination of cross-product of polynomial functions of maximum degree between the different MAppleT parameters (eq.…”
Section: Methodsmentioning
confidence: 99%